Customer Value and Its Influence on the Success of Hotel Marketing Strategies in Jember - Faozen; Jatmiko, Hadi (Media Wisata, 2023)
This research will discuss the influence of customer value as a success factor in hotel marketing strategies in Jember. So that through this research can contribute thoughts to the Jember hotel and restaurant union association and more specifically to hotel service business actors as a reference in taking policies in developing marketing strategies with value.   The purpose of this study is to analyze the influence of customer value in the success of hotel marketing strategies in Jember.  The data were analyzed by multiple linear regression by partial and simultaneous tests. The results of this study show that partially physical value variables, emotional value variables, intellectual value variables  have an influence but are not significant on the success of marketing strategies, while spiritual value variables have a significant influence on the success of marketing strategies,   simultaneously or together the variables of physical value, emotional value, intellectual value, spiritual value have a significant influence on the variable success of the hotel marketing strategy in Jember.